HISTORY AND STAGES OF THE DEVELOPMENT OF THE TRANSLATION STUDIES IN JAPAN - Sarybaeva, А А (Journal of Oriental Studies, 2016)
This article examines the history and stages of the development of translation studies in Japan. History of translation is closely associated with history of the state. China and Europe had enormous influence on development of the translation studies in Japan. And these mutual relations had an influence also into Japanese language and culture. And in ХХ eyelid development of the translation studies in Japan was associated with direction and level of the development of the country, by mutual relations with other states. Appeared the variety of translation types and translators.